Some lexical features of territorial English version of Nigeria - Baghana, Jerome; N. Prokhorova, Olga; G. Voloshina, Tatiana; N. Taranova, Elena; A. Glebova, Yana (International Journal of Engineering and Technology, 2018)
The article is devoted to the study of lexical features of the territorial version of the English language in Nigeria in different periods of its historical development. The authors analyze the linguistic and cultural peculiarities of the territorial version of the English language in Nigeria and depict some of its individual lexical units. The main aspect of the research stresses the importance of historical, cultural and linguistic interconnection as the single entity of language functioning in the era of globalization.Â